Financial Performance of Life Insurance Companies of Nepal - Bista, Purushotam (Journal of Kathmandu BernHardt College, 2022)
This study aims to analyze the financial performance of life insurance companies in Nepal and examine the effect of operating efficiency on solvency margin position and operating profit margin of selected life insurance companies have been analyzed. The study revealed that a mixed result in terms of the degree of effect of financial performance on the operating efficiency. There are both significant and insignificant effects of solvency margin and operating profit on operating efficiency of both sample insurance company. There are still major hurdles to overcome in order for Nepal to realize the growth potential of its insurance industry. Research could be conducted on the growth in the written premiums accounted by insures. The design and methods were applied according to the research type which is descriptive analysis. The data was extracted from annual reports and Nepal Beema Sasthan office. The findings were completely based on the data and facts. Secondary data were collected for analysis from 2010/11 to 2020/21 to find the financial performance, descriptive and causal-comparative research designs was employed for analysis secondary data. Different statistical tools like; standard deviation, correlation coefficient, multiple regression analysis, etc. and financial tools like ratio analysis, solvency ratio, earning per share, total assets, return on assets, insurance premium were used to evaluate the secondary data obtained from secondary sources. The findings of the research have shown the overall calculated financial ratios are good enough for better financial performance of selected life insurance companies in Nepal.